New Reebok strength cycle
Multiple Uses: Rehabilitation, sports specific, strength and cardiovascular training. Dual drive system offers unilateral and bilateral pedaling with easy switching. Unipedal mode allows for leg isolation rehabilitation. Improves hamstring to quadriceps strength ratio. Isolates and effectively works the hamstrings in a way that was not available previously. Increases caloric expenditure and enhances speed development for sports-specific athletes. Great cross-trainer for runners. Increases power and speed. Improves stride and form. Improves knee stability reducing incidence of injury. Increases leg coordination via timing as legs maintain180 degree opposite pedal position. Develops fast-twitch fibers which decreases hamstring tears and strains. Leg isolation training develops symmetry in both strength and technique. The workout effectively trains the brain to signal and recruit leg muscles in the most efficient pattern. Belt driven for smooth, quiet and clean operation. Advanced resistance lever for precision and incremental progression. Numerical marking system for seat height identification. Adjustable vertical and horizontal seat to handlebar range accommodates taller riders. Free wheel drive system. One-piece welded construction for a vibration-free durable frame.